FORWARD IMAGE COMPRESSION USING SEGMENT LEVEL-PLURALITY (FSLP) - Mohammed Salman, Tariq (Journal of Engineering and Sustainable Development, 2015)
To solve the problems of digital image processing for mapping, surveillance, recognition, video transmission and other areas used the image compression techniques. One way of image compression is image segmentation, there are number of segmentation methods based on the division and merging areas, which are widespread due the relative ease of implementation. The disadvantage of these methods is the appearance of segmentation faults structurally complex areas of pixels and lack of adaptation to the constraints of computational-enforcement resources, computation time and the vulnerability against changing brightness and contrast and weakness via the noise effect.